2009
DOI: 10.1606/1044-3894.3853
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Justice: A Systematic Review of the Social Work Literature

Abstract: Restorative justice is an alternative paradigm for dealing with the effects of crime and wrongdoing that seeks to bring healing to victims, offenders, and the community. Although a key element of social work's ethical code is the obligation to work toward social justice, this has been viewed primarily as efforts to ensure a fair distribution of resources and opportunities. Yet justice is also restorative in nature–-seeking to restore and enhance victims, offenders, and communities to fuller functioning. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Since the core values of RJ practice have spiritual and/or religious roots (Gumz & Grant, 2009), and religion and spirituality play a key role in the lives of many Muslims, social workers can utilize religious rituals and concepts that are culturally specific to the participants when dealing with RJ cases. To this end, social workers need to be familiar with the intersection and difference of culture, religion, and spirituality when handling RJ cases among Muslim immigrants in Western countries; because most often, it is difficult for a social worker in Western settings to differentiate what is cultural practice and what is religious rituals.…”
Section: Implications For Social Workmentioning
confidence: 99%
“…Since the core values of RJ practice have spiritual and/or religious roots (Gumz & Grant, 2009), and religion and spirituality play a key role in the lives of many Muslims, social workers can utilize religious rituals and concepts that are culturally specific to the participants when dealing with RJ cases. To this end, social workers need to be familiar with the intersection and difference of culture, religion, and spirituality when handling RJ cases among Muslim immigrants in Western countries; because most often, it is difficult for a social worker in Western settings to differentiate what is cultural practice and what is religious rituals.…”
Section: Implications For Social Workmentioning
confidence: 99%
“…Synthesizing 80 social work articles dealing with RJ, A recent systematic review concluded that the responsibilities of social workers as authors, researchers, and participants in RJ programs and practices remain significantly fairly unknown, and suggested for augmenting social work practice in RJ area (Gumz & Grant, 2009). With the core value of working with the vulnerable and suppressed populations for social justice, social workers have an excellent opportunity to be actively involved in RJ programs so that justice can be ensured for victims, offenders, communities, and their families.…”
Section: Implications For Social Workmentioning
confidence: 99%
“…Since the core values of RJ practice have spiritual and/or religious roots (Gumz & Grant, 2009), and religion and spirituality play a key role in the lives of many Muslims, social workers can utilize religious rituals and concepts that are culturally specific to the participants when dealing with RJ cases. To this end, social workers need to be familiar with the intersection and difference of culture, religion, and spirituality when handling RJ cases among active participation in dealing with RJ will minimize the gaps in the existing literature on social work practice, education, and research with Muslim population in the coming days (Husain, 2017).…”
Section: Implications For Social Workmentioning
confidence: 99%
“…Particularly in Canada, Native communities are increasingly bypassing the official system and managing justice processes on their own (Ross, 2006). Social workers have in recent years actively worked to bring such alternative practices into Western institutions (Gumz & Grant, 2009). …”
Section: Parallel Structuresmentioning
confidence: 99%